Perancangan Sistem Informasi Presensi Kuliah Pada Fakultas Ilmu Komputer - Robo, Salahudin; Tianotak, Moch Reza Barham; Trisno, T; Aryazillun, A; Tabelessy, Joseph Samuel (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
At the Faculty of Computer Science at Yapis University, Papua is currently using E-Learning for attendance and assignment systems, but there are still problems at the beginning of the semester, namely students always take attendance manually, because attendance is always manual, many problems arise such as fighting over each other when doing presence so it is very difficult if lost or damaged accidentally. The purpose of this research is to create a website attendance system for attendance activities that can expedite all attendance processes and the preparation of necessary reports from the faculty of computer science, the method used in this research is the development method, namely the waterfall, the design method, namely UML and the analysis method, namely PIECES, Functional Requirements in Student Information System Attendance is based on the level of system users. System users consist of three parts, namely students, lecturers and admin as administrator, The development of this special information system has the ability to streamline the process of recording attendance. The result of this research is that the newly developed system has the ability to meet needs by providing real-time attendance information. further development, namely this system can only be accessed through a browser on a computer for further development to be integrated so that it becomes multi-platform